Interleukin 6 receptor is not directly involved in regulation of body weight in diet-induced obesity with and without physical exercise - Minafra, Anna Rita; Chadt, Alexandra; Rafii, Puyan; Al-Hasani, Hadi; Behnke, Kristina; Scheller, Jürgen (Frontiers in Endocrinology, 2022)
High level of interleukin 6 (IL-6), released by adipocytes in an obesity-induced, low grade inflammation state, is a regulator of insulin resistance and glucose tolerance. IL-6 has also regenerative, anti-inflammatory and anti-diabetogenic functions, when secreted as myokine by skeletal muscles during physical exercise. IL-6 mainly activates cells via two different receptor constellations: classic and trans-signalling, in which IL-6 initially binds to membrane-bound receptor (IL-6R) or soluble IL-6 receptor (sIL-6R) before activating signal transducing gp130 receptor. Previously, we generated transgenic soluble IL-6 receptor +/+ (sIL-6R+/+) mice with a strategy that mimics ADAM10/17 hyperactivation, reflecting a situation in which only IL-6 trans-signalling is active, whereas classic signalling is completely abrogated. In this study, we metabolically phenotyped IL-6R deficient mice (IL-6R-KO), sIL-6R+/+ mice and wild-type littermates fed either a standard chow (SD) or a high-fat diet (HFD) in combination with a 6-weeks treadmill exercise protocol. All mice were subjected to analyses of body weight and body composition, determination of blood glucose and insulin level under fasting conditions, as well as determination of substrate preference by indirect calorimetry. Neither classic IL-6 nor trans-signalling do influence the outcome of diet-induced obesity, insulin sensitivity and glycaemic control. Furthermore, IL-6R deficiency is not impairing the beneficial effect of physical exercise. We conclude that the IL-6R does not play a requisite role in regulation of body weight and glucose metabolism in diet-induced obese mice.